The study of novel sequence alleles for Qatari population using ForenSeqTM DNA kit. Issue 1 (December 2019) - Almohammed, E.; Hadi, S.
Abstract: For the last three decades, Short Tanddem Repeat (STR) markers and capillary electrophoresis-based DNA sequencers have been the gold standard technology for human identification testing in the forensic field. Massive Parallel Sequencing (MPS) technology has enabled sequencing of several types of genetic loci in one multiplex including single nucleotide polymorphisms (SNPs) and STRs. One hundred and fifty (150) reference samples were profiled using the ForenSeq™ DNA Signature kit. PCR Primer Mix B for this kit was used containing autosomal/Y/X STRs and AISNPS, iSNPs and pSNPs loci. The analyses of the sequence of STR alleles in STRait Razor software were able to determine novel alleles in the autosomal, Y and X STR as well as SNPs loci. This increased number of alleles had a clear advantage in forensic casework. Several of these sequenced-based alleles had not been reported earlier in the literature. This study also confirmed some of the previously determined alleles in several loci. The results have clearly demonstrated the potential use of MPS methods to study the genetics of Qatari population.